Nanotechnology, Drug Delivery Systems and their Potential Applications in Hepatitis B Vaccines - Perazzo, Priscila (2015)
Since the Nobel Prize in Physiology or Medicine 1976 Baruch Blumberg and Irving Millman developed the first prophylactic plasma-derived hepatitis B vaccine - also considered the world´s first cancer vaccine- so much progress has been made in the development of new immunogenic and safe vaccines. However, improvements are still clearly required since vaccines currently available in the market produce mainly a humoral immune response, require cold storage, a three dose schedule, the costs of the vaccines are high, many developing or low-incoming countries display a poor compliance in vaccination programs, and 5-10% of the vaccinated individuals are poor or non-responders.To overcome such drawbacks, nanotechnology has emerged as a new platform for vaccine development. Nanocarrier-based delivery systems offer an opportunity to stimulate both humoral as well as cell-mediated responses and to induce mucosal and systemic immunity simultaneously. Furthermore, nanocarrier-based delivery systems avoid the need for sterile needles. This manuscript reviews the current knowledges on the vailable hepatitis B vaccines and introduces the recent advances in nanocarrier-based hepatitis B vaccine delivery systems. The challenges in the development of needle-free nanotechnologies are also discussed.